CARDIOPULMONARY CO-INFECTION BY STRONGYLOIDEA IN Puma yagouaroundi (CARNIVORA: FELIDAE) IN THE MUNICIPALITY OF CARLÓPOLIS – PR - Gonçalves Vieira, Fernando Emmanuel; Assis Soares, Juarez; Arlington Headley, Selwyn; Sasse, João Pedro; Brizola Martins, Leonardo; Utida, Maria Gabriela; Toledo Figueiredo, Guilherme de; Ferraz Caetano, Dyego Leonardo (Acta Biologica Brasiliensia, 2025)
This study investigated Strongyloidea co-infection in a jaguarundi (Puma yagouaroundi) that was hit by a car in Carlópolis, PR. The objective was to examine fecal and cardiopulmonary samples to identify helminths. The hypotheses were: I) Parasitism in carnivores naturally occurs in wild environments; II) Predation favors cardiopulmonary co-infections; III) The passage of helminths through the lungs causes histological inflammation. Hoffman’s sedimentation technique and flotation with hypersaturated NaCl solution were used for fecal analysis. In the lungs, the lower airways were scraped, sieved, and analyzed; lung fragments were macerated and left to sediment, while others were fixed in 10% formaldehyde for histopathological examination. The results revealed six helminths in the lungs: Oslerus sp., a pair of Angiostrongylus sp., and three Aelurostrongylus abstrusus, causing severe parasitic pneumonia. The study highlighted the relationship between these helminths and intermediate hosts, such as gastropods, as well as the role of domestic cats in maintaining these parasites in wildlife. Although based on a single case, the study concludes that integrated management measures are essential to mitigate these infections and promote the conservation of wild felines.